Effects of Experimental CO2 Enrichment on the PSII Photochemical Efficiency of Symbiodinium sp. in Acropora millepora - Ashleigh, McNie; Daniel, Breen; Vopel, Kay (London: Qeios Ltd., 2024)
Enrichment of seawater with CO2 decreases the concentration of the carbonate ion while increasing that of hydrogen and bicarbonate ions. We use pulse-amplitude-modulation (PAM) fluorometry to investigate whether, in the absence of warming, and in sub-saturating light, these changes affect the PSII photochemical efficiency of Symbiodinium sp. in the reef- building coral Acropora millepora. We assessed this experimentally with 30-min-interval saturation pulse analyses at 25 °C, a daily peak in the intensity of the photosynthetically active radiation (PAR) at ~65 μmol quanta m–2 s–1, and a seawater pCO2 that we gradually increased over nine days from ~496 to ~1290 μatm by injection of CO2-enriched air. Nine 14- day time series, which, except one, were recorded at the growing apices of a coral branch, revealed diel oscillations in the PSII photochemical efficiency characterized by a steep nocturnal decrease followed by a steep increase and peak in the morning, a daily minimum at midday (∆F/Fm’,midday), and a daily maximum at the onset of darkness at 19:00 h (Fv/Fm,19:00 h). An inadvertent shift in the position of one of the PAM fluorometer measuring heads revealed differences between the basal part and the growing coral apices of a coral branch in ∆F/Fm’midday and Qm. In ambient seawater (Control) Symbiodinium sp. exhibited a gradual decrease, over the course of the experiment, in ∆F/Fm’,midday, Fv/Fm,19:00 h, and the slope of the linear regression between the relative electron transport rate and the intensity of PAR (rETR/PAR). Although two of three successive experiments indicated that CO2 enrichment counteracted these trends, statistical analyses failed to confirm an influence of pCO2 on ∆F/Fm’,midday, Fv/Fm,19:00 h, and Qm, rendering this experiment inconclusive.
Keywords: CO2 enrichment; PAM fluorometry; photophysiology; reef-building coral; ocean acidification